Effects of the Decay of Incorporated Radioactive Phosphorus on the Transfer of the Bacteriophage SP82G Genome - McAllister, William T. (1973)
The last genetic markers to be transferred during bacteriophage SP82G infection have a higher sensitivity to the decay of incorporated radioactive phosphorous ((32)P) than those which are located on the proximal end of the genome. If (32)P decay is permitted to take place after DNA transfer is complete (in frozen infective centers) and in the absence of DNA replication, no dependence of marker sensitivity on map position is observed. These results indicate that the decay of incorporated (32)P leads to damages that prevent the efficient transfer of portions of the genome distal to the lesion. At 4 C, failure to transfer some portion of the genome occurs in 49% of all lethal events. Even though damages that prevent transfer of the genome are in themselves lethal, they do not prevent rescue of genetic markers on portions of the genome that are transferred. The portion of the genome that is transferred, is transferred at the same rate as an undamaged genome. We interpret these results to mean that double-strand breaks in the DNA are the lesions that prevent distal transfer and that single-strand breaks have little or no effect on the transfer of the bacteriophage SP82G genome.